TRACES OF UNREALITY: NUCLEAR ATTITUDES AND WASTE IN DON DELILLO’S UNDERWORLD - Knox, Tanner (Wake Forest University, 2026)
This thesis addresses a gap in scholarship related to Don DeLillo’s novel Underworld and its portrayal of nuclear weapons and waste during the Cold War period through the 1990s. In this article-length thesis, I examine the novel through the theoretical frame of hyperobjects developed by Timothy Morton. I establish that both nuclear weapons and waste function as hyperobjects within the world of DeLillo’s novel, stretching beyond the human frame of reference for both temporal and spatial vastness and causing humans to reconsider their place and relationship to the wider world. I make the claim that Underworld serves as a demonstration of the ways in which waste surpassed the nuclear weapons complex as the hyperobject of primary concern as the Cold War advanced closer to the turn of the century. DeLillo pairs these material objects with the psychological effects of both nuclear-age anxiety and the element of spectacle and fascination with both. In doing so, he positions waste as the primary threat to America, both tangibly and psychologically, as nuclear tensions descended from the fever pitch of the Cold War.
Keywords: Don DeLillo; Hyperobjects; Nuclear Waste; Underworld